2008
DOI: 10.1071/ea08132
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine improves egg production in black neck ostriches

Abstract: The important functions of L-carnitine are fostering the oxidation of long-chain fatty acids by mitochondria and stimulating protein-sparing action by increasing energy derived from lipids. The present study was conducted to investigate dietary effects of L-carnitine on egg production of breeder ostriches. Ninety black neck ostrich breeder birds (60 females and 30 males) were examined randomly (completely randomised design) within three treatments and five replicates for 7 months in breeding season. A basal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Due to the fact that young ostrich chicks can not use fibers as well as old ostriches (Cooper et al, 2004), here synbiotic may has contributed in development of healthy microflora in the hindgut, to get more energy from the nutrient fermentation in the cecum and consequently have improved the performance of the birds. In contrast to these results, Gri et al (2008) failed to show any significant impact of probiotics in rhea chicks. The addition of probiotic to diets may influence broiler weight gain (Langhout, 2000).…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…Due to the fact that young ostrich chicks can not use fibers as well as old ostriches (Cooper et al, 2004), here synbiotic may has contributed in development of healthy microflora in the hindgut, to get more energy from the nutrient fermentation in the cecum and consequently have improved the performance of the birds. In contrast to these results, Gri et al (2008) failed to show any significant impact of probiotics in rhea chicks. The addition of probiotic to diets may influence broiler weight gain (Langhout, 2000).…”
Section: Resultscontrasting
confidence: 92%
“…BW, FCR) (Mohan et al, 1996;Yeo and Kim, 1997;Kabir et al, 2004;Gunal et al, 2006;Nayebpor et al, 2007;Paryad and Mahmoudi, 2008). In this study, the higher growth performance observed in the ostrich chicks consuming the diets containing probiotics may be due to a change in their gastrointestinal tract microbiota populations, as reported for broiler chickens (Schrezenmier and Vrese, 2001;Gunal et al, 2006;Alloui et al, 2013). Dietary Lcarnitine supplementation (50 mg kg -¹) has been found an increase in feed intake (Sayed et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation